Determination of the ovine ovarian reserve during the prenatal and neonatal periods - Isam B Sharum (Asian Pacific Journal of Reproduction, 2023)
Objective: To determine the ovine ovarian histomorphology and follicular staging at various age periods in Awassi breed. Methods: Ovaries were collected from prenatal fetuses [gestational age (95±5) days], neonatal (day 0), and prepubertal ewe lambs (two and four months of age); each age group included six animals. Ovaries (n=12, each group) were dissected and processed for hematoxylin and eosin staining. Stained sections (n=24, each group) were imaged and utilized for histomorphology assessment, follicle measurement, and classification. Results: Prenatal ovaries were mainly enriched with primordial follicles accompanied by a lower proportion of primary follicles. In addition to primordial and primary follicles, neonatal ovaries demonstrated a proportion of centrally located multilayered and antral follicles. In comparison with neonatal ovaries, the proportion of multilayered and antral follicles was significantly higher in the ovaries of two-month-old lambs; conversely, the proportion of peripherally situated primordial follicles dramatically declined compared to that of earlier age of lamb. Although there was no statistical variation in the sizes of primordial follicles across groups, the mean diameter of the primary follicle in the prenatal ovaries was substantially smaller than in postnatal ovaries. Compared to the neonatal ovaries, the size of the multilayered and antral follicles in the prepubertal ovaries was substantially larger. Conclusions: The earliest follicular developmental stages were established prenatally whereas the advanced growth stages started in the neonatal period and greatly increased in the prepubertal period.